The role of C4d deposition in the diagnosis of antibody‐mediated rejection after lung transplantation. Issue 4 (11th November 2017) - Aguilar, P. R.; Carpenter, D.; Ritter, J.; Yusen, R. D.; Witt, C. A.; Byers, D. E.; Mohanakumar, T.; Kreisel, D.; Trulock, E. P.; Hachem, R. R.
Abstract : Antibody‐mediated rejection (AMR) is an increasingly recognized form of lung rejection. C4d deposition has been an inconsistent finding in previous reports and its role in the diagnosis has been controversial. We conducted a retrospective single‐center study to characterize cases of C4d‐negative probable AMR and to compare these to cases of definite (C4d‐positive) AMR. We identified 73 cases of AMR: 28 (38%) were C4d‐positive and 45 (62%) were C4d‐negative. The two groups had a similar clinical presentation, and although more patients in the C4d‐positive group had neutrophilic capillaritis (54% vs. 29%, P = .035), there was no significant difference in the presence of other histologic findings. Despite aggressive antibody‐depleting therapy, 19 of 73 (26%) patients in the overall cohort died within 30 days, but there was no significant difference in freedom from chronic lung allograft dysfunction (CLAD) or survival between the two groups. We conclude that AMR may cause allograft failure, but that the diagnosis requires a multidisciplinary approach and a high index of suspicion. C4d deposition does not appear to be a necessary criterion for the diagnosis, and although some cases may respond initially to therapy, there is a high incidence of CLAD and poor survival after AMR. Abstract : In this retrospective single‐center study, complement component 4d deposition does not appear to be a necessary criterion for the diagnosis of antibody‐mediated rejection after lung transplantation.